PENGARUH PERPUTARAN MODAL KERJA, ADVERTISING (PERIKLANAN), DAN KEBIJAKAN DIVIDEN TERHADAP RETURN SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019 -2022 - Sururi, Fairira Anindia; Sari, Lita Permata; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Banking is said to support the country's economy, especially in contemporary times like today, because the role of banking as a driver of the country's economy is very important. The purpose of this research is to determine the effect of working capital turnover, advertising (advertising), and dividend policy on stock returns with profit ability as an intervening variable. This research uses quantitative research methods. The populations in this research are banking companies listed on the Indonesia Stock Exchange (BEI) with a sample of 8 companies. The sampling technique used in this research was purposive sampling. The data analysis and hypothesis testing in this research used the Partial Least Square Structural Equation Model (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that working capital turnover has an insignificant negative effect on profitability, advertising has an insignificant negative effect on profitability, dividend policy has a positive and significant effect on profitability, working capital turnover has an insignificant negative effect on stock returns , Advertising has an insignificant negative effect on stock returns, dividend policy has an insignificant negative effect on stock returns, Profitability has an insignificant negative effect on stock returns. The results of the indirect influence hypothesis test show that the working capital turnover variable has an insignificant negative effect on stock returns through profitability, advertising has an insignificant negative effect on stock returns through profitability, and dividend policy has an insignificant negative effect on stock returns through profitability.